Measurement of spherical tokamak plasma compression in the PCS-16 magnetized target fusion experiment - S.J. Howard; M. Reynolds; A. Froese; R. Zindler; M. Hildebrand; A. Mossman; M. Donaldson; T. Tyler; D. Froese; C. Eyrich; K. Epp; K. Bell; et al. (Nuclear Fusion)
A sequence of magnetized target fusion devices built by General Fusion has compressed magnetically confined deuterium plasmas inside imploding aluminum liners. Here we describe the best-performing compression experiment, PCS-16, which was the fifth of the most recent experiments that compressed a spherical tokamak plasma configuration. In PCS-16, the plasma remained axisymmetric with $δ B_pol/B_pol \lt 20%$ to a high radial compression factor ( $C_\mathrm R \gt 8$ ) with significant poloidal flux conservation (77% up to $C_\mathrm R = $ 1.7, and ${≈}30%$ up to $C_\mathrm R = 8.65$ ) and a total compression time of 167 $μs$ . Magnetic energy of the plasma increased from 0.96 kJ poloidal and 17 kJ toroidal to a peak of 1.14 kJ poloidal and 29.9 kJ toroidal during the compression, while the thermal energy was in the range of 350 ± 25 J. Plasma equilibrium was a low- β state with $β_tor ≈ 4%$ and $β_pol ≈ 15%$ . Ingress of impurities from the lithium-coated aluminum wall was not the dominant effect. Neutron yield from D-D fusion increased significantly during compression. Thermodynamics during the early phase of compression ( $C_\mathrm R \lt 1.7$ ) were consistent with increasing Ohmic heating of the electrons due to a geometric increase in the current density at near-constant resistivity, and with increasing ion cooling that approximately matched ion compression heating power. Ion cooling by electrons was significant because the electrons were much cooler than the ions ( $T_\mathrm e = 200\,eV, T_\mathrm i = 600\,eV$ ). Magnetohydrodynamic simulations were used to model the emergence of instabilities that increase electron thermal transport in the final phase of compression. Conditions for ideal stability were actively maintained during compression through a current ramp applied to the central shaft and, after this current ramp reached its peak two-thirds of the way through compression, we measured a transition in plasma behavior across multiple diagnostics.